The Controller as Lean Leader - Sondergelt, Sue (Productivity Press, 2017)
Traditional accounting systems have become inadequate for today's increasingly competitive global manufacturing environment. They are too complex and too focused on past performance. As manufacturing techniques change and become less labor intensive, accounting methods must also evolve. Regardless of what you call it, Lean accounting is a managemen.